Práticas corporativas para um sistema eficaz de Compliance: uma abordagem para empresas de médio porte - Souza, Joice de (Universidade do Vale do Rio dos Sinos, 2019)
This study aims to analyze corporate practices that can be used by medium sized companies to establish an effective compliance environment. The qualitative research was conducted by interviewing executives from ten companies based in Serra Gaúcha and Great Porto Alegre in the State of Rio Grande do Sul, from May to October 2018, seeking to identify the practices that they use to create an effective compliance environment. The parameter of these practices consisted of documents developed by national and international bodies that are benchmarks for the subject, as well as related publications. The results identified practices pointed out by the managers as the most adequate, or those used in the companies that enable a better result to conform with a compliance program, making it effective. The identified practices were related to the proposed guidelines based on the literature and they showed that for each guideline there was at least one effective practice in the activities of the companies object of this research. This search highlights a better understanding of the topic of compliance for medium sized companies, offered by the synthesis of routine practices used by them and that meet the requirements of the guidelines drawn up by bodies that are a benchmark for compliance issues. In terms of management, the set of practices found related to the basic guidelines of an effective compliance program can help managers of medium sized companies understand the importance of using such programs for the vitality of their business.
Keywords: Compliance; Programas de compliance; Lei anticorrupção; Controles internos; Compliance; Compliance programs; Anti-corruption law; Internal controls; ACCNPQ::Engenharias::Engenharia de Produção